A randomised controlled non-inferiority trial of primary care-based facilitated access to an alcohol reduction website (EFAR Spain): the study protocol. Issue 12 (31st December 2014) - López-Pelayo, Hugo; Wallace, Paul; Segura, Lidia; Miquel, Laia; Díaz, Estela; Teixidó, Lidia; Baena, Begoña; Struzzo, Pierliugio; Palacio-Vieira, Jorge; Casajuana, Cristina; Colom, Joan; Gual, Antoni
Abstract : Introduction: Early identification (EI) and brief interventions (BIs) for risky drinkers are effective tools in primary care. Lack of time in daily practice has been identified as one of the main barriers to implementation of BI. There is growing evidence that facilitated access by primary healthcare professionals (PHCPs) to a web-based BI can be a time-saving alternative to standard face-to-face BIs, but there is as yet no evidence about the effectiveness of this approach relative to conventional BI. The main aim of this study is to test non-inferiority of facilitation to a web-based BI for risky drinkers delivered by PHCP against face-to-face BI. Method and analysis: A randomised controlled non-inferiority trial comparing both interventions will be performed in primary care health centres in Catalonia, Spain. Unselected adult patients attending participating centres will be given a leaflet inviting them to log on to a website to complete the Alcohol Use Disorders Identification Test (AUDIT-C) alcohol screening questionnaire. Participants with positive results will be requested online to complete a trial module including consent, baseline assessment and randomisation to either face-to-face BI by the practitioner or BI via the alcohol reduction website. Follow-up assessment of risky drinking will be undertaken online at 3 months and 1 year using the full AUDIT and D5-EQD5 scale. Proportions of risky drinkers in each group will be calculated and non-inferiority assessed against a specified margin of 10%. Assuming reduction of 30% of risky drinkers receiving standard intervention, 1000 patients will be required to give 90% power to reject the null hypothesis. Ethics and dissemination: The protocol was approved by the Ethics Commmittee of IDIAP Jordi Gol i Gurina P14/028. The findings of the trial will be disseminated through peer-reviewed journals, national and international conference presentations. Trial registration number: ClinicalTrials.gov NCT02082990 .